2015
DOI: 10.1371/journal.pone.0142408
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Variants of SCN1A and EPHX1 Influence Plasma Carbamazepine Concentration, Metabolism and Pharmacoresistance in a Population of Kosovar Albanian Epileptic Patients

Abstract: AimThe present study aimed to evaluate the effects of gene variants in key genes influencing pharmacokinetic and pharmacodynamic of carbamazepine (CBZ) on the response in patients with epilepsy.Materials & MethodsFive SNPs in two candidate genes influencing CBZ transport and metabolism, namely ABCB1 or EPHX1, and CBZ response SCN1A (sodium channel) were genotyped in 145 epileptic patients treated with CBZ as monotherapy and 100 age and sex matched healthy controls. Plasma concentrations of CBZ, carbamazepine-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 73 publications
1
28
2
1
Order By: Relevance
“…We did not observe any genomewide significant associations with CBZ metabolic ratio ( Figure 3). 16 We did not replicate this finding (rs2234922; P = 0.303) but we observed a nominally significant association between an intronic EPHX1 SNP (c.365-2139T>C) and CBZ metabolic ratio (rs4653689; P = 1.1 × 10-4). Polymorphisms in CYP3A4 and EPHX1 have been shown to associate with interindividual variability of CBZ metabolism.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…We did not observe any genomewide significant associations with CBZ metabolic ratio ( Figure 3). 16 We did not replicate this finding (rs2234922; P = 0.303) but we observed a nominally significant association between an intronic EPHX1 SNP (c.365-2139T>C) and CBZ metabolic ratio (rs4653689; P = 1.1 × 10-4). Polymorphisms in CYP3A4 and EPHX1 have been shown to associate with interindividual variability of CBZ metabolism.…”
Section: Resultscontrasting
confidence: 56%
“…It had been reported that homozygous carriers of the EPHX1 c.416A>G SNP (rs2234922) seemingly show a reduced CBZ metabolism, as measured by a significantly decreased metabolic ratio. 16 We did not replicate this finding (rs2234922; P = 0.303) but we observed a nominally significant association between an intronic EPHX1 SNP (c.365-2139T>C) and CBZ metabolic ratio (rs4653689; P = 1.1 × 10-4).…”
Section: Resultscontrasting
confidence: 56%
“…Furthermore, evidence of microsomal epoxide hydrolase activity at or near the blood-brain barrier has been reported (Ghersi-Egea et al, 1994). Carbamazepine, phenobarbital, and phenytoin are three xenobiotics with well characterized metabolic pathways involving epoxide hydrolase, with recent evidence suggesting that single nucleotide polymorphisms in the microsomal epoxide hydrolase gene EPHX1 influence carbamazepine exposure in vivo (El-Sherbeni and El-Kadi, 2014;Zhu et al, 2014;Daci et al, 2015).…”
Section: Epoxide Hydrolasesmentioning
confidence: 99%
“…Secondly, genetic differences in different races may be also an important factor. Thirdly, different treatments, mono-or combination AEDs, may also affect treatment results of AEDs [17,36,37]. A SNP-SNP interaction, rs7598931 and rs12233719 located in SCN2A and UGT2B7 separately, associated with VPA responses was first found.…”
Section: Biomed Research Internationalmentioning
confidence: 99%